Consumers' disposition of meaningful possessions through storage - Smestad, Bente (2006)
30 years after Jacoby (1976) defined consumer behaviour to include disposition, researchers still comment on the lack of research in this area. Whilst disposition in general has received scant attention, especially storage as an alternative means of disposition has been efficiently ignored. This dissertation seeks to contribute to filling a part of the big void in this knowledge by exploring storage of meaningful possessions in particular. In doing this, the dissertation first offers a review of the related literature, namely on disposition, self-concept, and meaning. 12 middle-aged and elderly Norwegian consumers were interviewed, providing valuable insight into their relevant storing behaviour. The study illustrates that the consumers attached sacred-, social-, and hedonic meanings to their possessions, which together constituted the main determining factor for the decision to store. Reasons for the possession being stored instead of being used or displayed were detected to be its coming out of use and it being perceived as inappropriate. Further, a desire to keep it in the family, and the owner's conscience were found to affect the decision to store instead of using other means of disposition. There are provided evidence suggesting that storage can function both as an individual means of disposition and as a divestment ritual. This is due to the fact that the possessions' meanings were affected by the prolonged storage to different extents and in different directions. A framework and subsequent model are proposed, concerning the factors that influence a consumer's decision to store her/his meaningful possessions instead of using other means of disposition.